2016
DOI: 10.1016/j.ymgmr.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The levels of urinary glycosaminoglycans of patients with attenuated and severe type of mucopolysaccharidosis II determined by liquid chromatography-tandem mass spectrometry

Abstract: Glycosaminoglycans (GAGs) play important roles on the regulation of extracellular signaling, neuronal development, and cartilage maintenance. The extracellular concentration of total GAGs has been used as an established measure for the diagnosis of mucopolysaccharidoses (MPSs). Heparan sulfate (HS), Dermatan sulfate (DS) and chondroitin sulfate are known to be elevated in the GAGs under pathological conditions associated with MPS. Furthermore, the selective accumulation of disease-specific one of, or a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The LC‐MS/MS method can also be used to differentiate the subtypes of MPS II, and the concentration of HS is the main factor used to distinguish the mild form of MPS II from the severe form. Mashima et al ( reported that among patients who received ERT with confirmed elevation of antibody titers, the concentration of HS in the urine of patients with the severe form was higher than that in those with the mild form of MPS II. Consistently, the concentrations of HS detected in the samples of our patients with the severe form of MPS II were more than 60 times higher than those of the patients with the mild form (446.6 vs. 7.3 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LC‐MS/MS method can also be used to differentiate the subtypes of MPS II, and the concentration of HS is the main factor used to distinguish the mild form of MPS II from the severe form. Mashima et al ( reported that among patients who received ERT with confirmed elevation of antibody titers, the concentration of HS in the urine of patients with the severe form was higher than that in those with the mild form of MPS II. Consistently, the concentrations of HS detected in the samples of our patients with the severe form of MPS II were more than 60 times higher than those of the patients with the mild form (446.6 vs. 7.3 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…The "Skeletal" group is caused by KS and includes patients with MPS IV presenting with joint laxity, genu valgum, odontoid hypoplasia, extreme short stature, and skeletal dysplasia (Hendriksz et al, 2015). The amounts of the affected GAG-derived disaccharides in the different types of MPS have been reported to be associated with the clinical manifestations, severity, and onset of MPS disorders (Auray-Blais et al, 2016;Mashima, Sakai, Tanaka, Kosuga, & Okuyama, 2016;Tomatsu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "skeletal" group is caused by KS and includes MPS IVA, with manifestations of joint laxity, odontoid hypoplasia, genu valgum, extreme short stature, and skeletal dysplasia. The amounts of the affected GAG-derived disaccharides have been associated with the clinical presentations, onset, and severity of MPS disorders [25][26][27][28]. Settembre et al [29] reported that GAG accumulation in lysosomes disrupts autophagy, which is important for chondrocyte metabolism during endochondral ossification, leading to chondrocyte viability and thus the development of skeletal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In more than one study, ADA-positive patients are associated to higher uGAGs levels and in some cases to poorer outcome [18,19,32,36,133,196,214,215]. No impact was seen for vestronidase [21].…”
Section: Immunogenicitymentioning
confidence: 98%